THE INFLUENCE OF LIVE STREAMING AND DISCOUNTS ON PURCHASE DECISIONS AT TIKTOK SHOP - Syarifah Azzahra, Annisa; Citra Rahayu Indraswari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The purpose of this research is to find out how live streaming features and discounts influence TikTok Shop Generation Z consumers, who are domiciled in Jakarta and aged between 18 and 24 years in purchasing decisions. With a total of 270 respondents, this research uses quantitative methods, employing multiple linear regression analysis. The findings show that the live streaming features positively and significantly influence the purchasing decisions of TikTok Shop Generation Z consumers. Additionally, discounts also have a positive and significant influence on consumer purchasing decisions. Both live streaming features and discounts simultaneously influence the purchasing decisions of TikTok Shop Generation Z consumers in a positive and significant.